Liderazgo en la toma de decisiones del Gad Municipal del cantón Salcedo. - Fonseca Chiliquinga, Danny Santiago (2023)
The leadership in decision making has been crucial part for organizational development of the Canton, because from this entity has moved a number of sources progress, in such a way that it has contributed to capital development. The present research work has been developed at Municipal GAD Salcedo Cantón of the province of Cotopaxi within the period 2023 - 2027; which aims to diagnose the relationship of leadership and decision making by managers and departmental heads, for which it has been proposed as an objective: To develop leadership strategies for making decision of departmental heads. For development of this research work, a quantitative, non exploratory, cross-sectional approach was used, which allowed to collection information through application of a questionnaire consisting of 24 questions, which was applied to 33 members of different departmental directorates to GAD Municipa Therefore, by collected information, it has become evident that there are several shortcomings on the part of this public entity in relation to leadership and making decision. In order to determine a viable resource for public entity, a series of strategies have been developed to provide solutions, which is based on programming regular activities for collaborators, in order to develop skills and create comfortable environments.